American penology: a history of control - Blomberg, Thomas G. (Aldine Transaction)
Public punishment in Colonial America (1600-1790) -- Penal code reform in period of transition (1790-1830) -- Age of penitentiary in nineteenth-century America (1830-1870s) -- Progressivism and reformatory, parole, and probation (1880s-1920s) -- Progressivism and juvenile court (1900-1960s) -- Twentieth-century rehabilitative ideal and "correctional" system (1900- -- 1960s) -- Prison subcultures (1950s-1960s) -- Prisoner rights in age of discontent (1960s-1970s) -- Decentralizing corrections (1960s-1970s) -- Conservatism and law-and-order punishment (1980s-1990s) -- Penal system as surrogate institution for special populations -- Punishment in millennial age -- Conclusion